Factors Related to The Family Latrine Use Coverage in Sabilambo Village Kolaka District - Yanti, Fitri; Jayadipraja, Erwin Azizi; Kandari, Maryam; Rahmawati, Rahmawati; Amasyah, Munawir (YCAB Publisher, 2025)
Background:Among the seven sub-districts within the Kolaka Health Center Working Area, Sabilambo Village exhibited the lowest progress in family latrine ownership. Objectives:This study aims to identify the factors associated with the coverage of family latrine use in Sabilambo Village, Kolaka Regency. Methods:This research employed an analytical approach using a cross-sectional study design. The study population comprised all heads of families in Sabilambo Village, totaling 1.105 families, from which a sample of 92 families was selected using simple random sampling techniques. Results:The Chi-Square test results indicated a significant relationship between knowledge (X²count = 13.086 > X²table = 3.481), household income (X²count = 18.335 > X²table = 3.481), people's habits (X²count = 21.486 > X²table = 3.481), and the role of the local government (X²count = 25.213 > X²table = 3.481) with the coverage of family latrine use in Sabilambo Village, Kolaka Regency. Conclusion:The findings indicate that knowledge, household income, community habits, and the role of local government significantly influence the coverage of family latrine use in Sabilambo Village. To address these issues, it is recommended that community members enhance their awareness of the importance of proper and healthy latrine use, fostering a behavioral shift from the use of unhealthy latrines to healthier alternatives. Keywords:knowledge; household income; community habits; government role; family latrine use